Indigenous Law and the Politics of Kincentricity and Orality - Kearney, Amanda (Springer Nature, 2023)
This Palgrave Pivot strives to recount and understand Indigenous Law, as set within a remote community in northern Australia. It pays close attention to the realpolitik and high-level political functioning of Indigenous Laws, which inspires a discussion of how this Law models the relational, influences governance and emplaces people in an ordered kincentric lifeworld. The book argues that Indigenous Law can be examined for the ways in which it is a deliberate, stabilizing and powerful force to maintain communal order in relation to Country, a counter framing to popular and 'soft law or soft power asset' visions of such Laws often held in the national and international imaginary. It is the latter which too often renders this knowledge esoteric and relinquishes it to a category of lore or folklore. This is an open access book.